Vaccination Failure in Eradication and Control Programs for Bovine Viral Diarrhea Infection - Antos, Aleksandra; Miroslaw, Pawel; Rola, Jerzy; Polak, Miroslaw Pawel (Frontiers in Veterinary Science, 2021)
Vaccination against bovine viral diarrhea (BVD) is one of the key elements to protect cattle herds from this economically important disorder. Bovine viral diarrhea virus (BVDV) is a pestivirus infecting animals at all ages with significant impact on reproductive, digestive, and respiratory systems. Financial burden caused by this pathogen prompts many farmers to introduce vaccination as the control and prophylactic measure especially when persistently infected (PI) individuals, being the main source of the virus in the herd, are removed after test-and-cull approach. The aim of this study was to analyze serological response in cattle herds where without or despite the removal of PI animals and the introduction of the whole herd vaccination, new PI calves were identified. Overall seroprevalence in 5 vaccinated herds was 91.7% and 83.3% using ELISA and virus neutralization test, respectively. Despite high titers for both vaccine and field strains of BVDV in analyzed herds the analysis of comparative strength of neutralization indicated that 41.4% of positive samples did not have a predominant titer against one specific subtype of BVDV. In 3 herds BVDV-1b subtype was identified while in 2 others it was BVDV-1d while the vaccine used was based on BVDV-1a which was never identified in Poland so far.